Isolated prostatic utricle - Ramachandra Mukunda; Bendre Pradnya; Redkar Rajeev; Taide Devendra (Wolters Kluwer Medknow Publications, 2009)
Complete excision of a prostatic utricle through posterior sagittal rectum retracting approach is reported in an infant.